Simulation of Smith fuzzy PID temperature control in enzymatic detection of pesticide residues - Jun, Sun; Meixia, Zhang; Zhengming, Li; Xiaohong, Wu (International Journal of Agricultural and Biological Engineering, 2015)
Enzyme activity is easily influenced by temperature, resulting in accuracy decline of enzymatic detection of pesticide residues. In this study, a controller which controls the internal temperature of the pesticide residues detector was simulated and analyzed. The mathematical model of temperature control was established by the application of the heat transfer theory. Against models with characteristics of large inertia and large hysteresis, a Smith fuzzy PID controller was proposed by combining the Smith predictor with the fuzzy PID controller. The PID controller, the fuzzy PID controller, and the Smith fuzzy PID controller were simulated in MATLAB, respectively in the same step signal given with amplitude of 1. The performance indexes (percent overshoot, settling time, and steady-state error) of various controllers were presented as follows: the PID controller (19%, 250 s, 0.0001), the fuzzy PID controller (11%, 450 s, 0.0001), and the Smith fuzzy PID controller (0%, 140 s, 0). From 1 180 s to 1 230 s, an interference signal with amplitude of 5 was added to test interference immunity. The PID controller and the fuzzy PID controller had greater fluctuations, but the Smith fuzzy PID controller had no fluctuations. The recovery time of each controller was described below: the PID controller (200 s), the fuzzy PID controller (300 s), and the Smith fuzzy PID controller (120 s). Robustness of the controller was tested by adjusting the time constant and the delay time. The performance indexes of the controllers were shown as follows: the PID controller (38%, 450 s, 0.0001), the fuzzy PID controller (23%, 880 s, 0.00025), and the Smith fuzzy PID controller (1%, 150 s, 0). The results of simulation showed that the performance indexes of the Smith fuzzy PID controller were better than that of the other controllers. Besides, the robustness and interference immunity are stronger than other controllers as well. The Smith fuzzy PID controller can accurately control the internal temperature of the pesticide residues detector to provide the best temperature for enzymatic detection. DOI: 10.3965/j.ijabe.20150801.007 Citation: Sun J, Zhang M X, Li Z M, Wu X H. Simulation of Smith fuzzy PID temperature control in enzymatic detection of pesticide residues. Int J Agric & Biol Eng, 2015; 8(1): 50－56.